PROSES PERUMUSAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 2 TAHUN 2011 TENTANG PERUBAHAN UNDANG-UNDANG NOMOR 2 TAHUN 2008 TENTANG PARTAI POLITIK - , Suprih Hidayat, S.Sos.; , Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research theme was the formulation process of the Republic of Indonesia Act No. 2 of 2011 concerning Amendment to Law No. 2 of 2008 on Political Parties. There were two research questions posed to conduct the research which were